Long-term changes in hydrographic conditions in northern Adriatic and its relationship to hydrological and atmospheric processes - Supić, N.; Grbec, B.; Vilibić, I.; Ivančić, I. (Annales Geophysicae, 2004)
A very long data series (1921–2000) of hydrographic parameters (temperature, salinity and density) collected in surface and bottom layers at a station in the coastal zone in the northeastern Adriatic was analyzed. Seasonal and interannual variability of the three parameters is described on the basis of monthly and yearly averages. The seasonal cycles obtained were found to be typical for the northern Adriatic. Interannual analysis showed that there was no trend in temperature, salinity and density in the region during the interval analyzed. The long-term series of yearly means of hydrographic parameters were related to the long-term series of yearly means of several hydrological/atmospheric parameters using different time lags of between 0 and 4 years. These parameters are surface heat flux gained by insolation Qs computed for Trieste, precipitation P in Trieste, Po River discharge rate R and two atmospheric oscillation indexes, a Mediterranean Oscillation (MO) index and North Atlantic Oscillation (NAO) index. At zero time lag the interannual changes at the surface were found to be significantly related to changes in the Qs and NAO index (temperature) and R (salinity and density). At the same time lag the changes in the bottom were found to be related to the MO index (temperature, salinity and density). Additionally, bottom salinity and density were significantly related to R at a time lag of 1 year. Key words. Oceanography: Physical (air-sea interactions; hydrography)